Cultural scripts and gendered parenting roles across East-West borders. - Ruottunen, Sonja (Gender, Place & Culture: A Journal of Feminist Geography, 2026)
Migration reshapes but does not automatically transform gendered roles within families. Based on 35 semi-structured interviews conducted in 2018–2019, this article examines how Russian-speaking migrant parents in Finland construct and negotiate gendered parenting roles through cultural scripts. The analysis shows that parents consistently frame 'good parenting' as requiring cooperation between mothers and fathers but justify this through essentialised discourses of innate gender difference: mothers as caring and soft, fathers as strict and demanding. These gendered roles persist across different family forms and are reinforced both by national imaginaries contrasting 'East' and 'West' and by the continued dominance of heteronormative two-parent ideals. While some parents adapted their scripts in response to separation, institutional contexts, or Finnish parenting discourses, overall, the findings highlight the resilience of gendered parenting roles as an essentialised truth within migrant families. The article contributes to scholarship on migration, gender, and parenting by showing how essentialised gender discourses persist within cultural scripts of parenting during migration while still allowing room for negotiation and change.